228k views
5 votes
Simplify the expression.

30 - [(7 - 4) + (10 - 22)
30 - [(7 - 4) + (10 - 22)2 =

(ANSWER QUICKLY)

Simplify the expression. 30 - [(7 - 4) + (10 - 22) 30 - [(7 - 4) + (10 - 22)2 = (ANSWER-example-1
User Leonidas
by
5.4k points

2 Answers

1 vote

Answer:

-51

Explanation:

30 - [(7 - 4) + (10 - 22)]² = ?

30 - [3 + (-12)]² = ?

30 - [-9]² = ?

30 - 81 = ?

= -51


\tt{ \green{P} \orange{s} \red{y} \blue{x} \pink{c} \purple{h} \green{i} e}

User MikeyB
by
5.5k points
1 vote

Answer:

-51

Explanation:

30 - (3 + (-12))^2

30 - (-9)^2

30 - 81

-51

User SecretIndividual
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.